Peran Masyarakat Dalam Kreatif Merawat Lingkungan: (Undang-Undang Nomor 32 Tahun 2009 Tentang Pengelolaan Lingkungan Hidup) - Edi Kristianta Tarigan; Muhammad Khadafi; Darmayanti, Erni; Mujib Medio Annas; Lesmana, Adinda Putri (LPPM Universitas Potensi Utama, 2023)
The environment is all objects and forces and conditions, including humans and their actions, which are present in the space where humans exist and affect the survival and well-being of humans and other living organisms. Research Methods This type of community service is a form of legal counseling by delivering material and providing legal knowledge through legal counseling and discussions and questions and answers which will be held at Dolu Sidebuk-debuk on Saturday, 10 to 11 December 2022 from 13.00 WIB to 13.00 WIB completed, attended by the local community and the village head of Dolu sidebuk-debuk. The data analysis used is qualitative, using the type of presentation of normative law and the nature of the presentation is descriptive. The approach used to answer the presentation is the Law. The data collection method in this study was carried out by counseling and discussion then taking and concluding some of the writings contained in the Act, articles, books as well as some legal writing results related to the discussion. Efforts to protect and manage the environment are a conditio sine qua non, which means that causes can be determined for each effect and each cause has an influence on the occurrence of an effect to be carried out consistently in sustainable national development. Environmental law is a reliable tool for protecting and managing the environment because environmental law apart from having a prevention function also has a law enforcement function whenever damage and/or damage to the environment is caused by legal subjects as a result of business and/or or the activities they do.